Innovative Comparison on the Performance of TiCN Coated Drill Bit and Uncoated Drill Bit in the Novel CNC Drilling of LDX 2205 Duplex Stainless Steel for Maximizing Material Removal Rate (Journal of Pharmaceutical Negative Results, 2022)
Aim: This research focuses on increasing the Material Removal Rate (MRR) by comparing the performance of conventional uncoated HSS drill bit and TiCN drill bit during the Novel CNC drilling of LDX 2205 Duplex Stainless Steel. Materials & Methods: Materials used for the drill bits in this research are Titanium Carbonitride (TiCN) coated HSS drill bit and uncoated HSS drill bit. LDX 2205 Duplex Stainless Steel material was used as workpiece. A total of 40 specimens were divided into 2 groups with 80% G-Power calculator, to measure the MRR of two drill bits in novel CNC drilling machine. Cutting force, spindle speed, tool geometry, rate of feed were the controlled factors. Results: The observed results for each drill bit were recorded and analyzed using SPSS software. Final experimental values of MRR were investigated and obtained, having mean MRR value of 0.052645 g/s for the HSS drill bit and mean MRR value of 0.064765 g/s for the TiCN drill bit. These values were obtained with a significance level of 0.032 which is less than 0.05 (p<0.05). Conclusion: Within the limits of this study, TiCN drill bit has comparatively higher MRR than the HSS drill bit in the novel CNC drilling of LDX 2205 duplex stainless steel.